Green human resource management and pro-environmental behaviour nexus with the lens of AMO theory - Tabeer Iftikar; Saddam Hussain; Muhammad Imran Malik; Shabir Hyder; Muhammad Kaleem; Adeel Saqib (Cogent Business & Management, 2022)
The purpose of this paper was to examine the extent to which green HRM impacts the pro-environmental behavior of employees via the mediation of Green Entrepreneurship and the moderation of Green Self-Efficacy in the hospitality sector of Pakistan. Research design included questionnaires and the study setting was cross-sectional. Respondents of the study were 4 and 5-star hotel employees of Islamabad city of Pakistan. However, a 205-sample size was taken from the population to collect primary data for deriving results. Data were collected from 205 hotel employees, and there were no incomplete data. Using SEM through Smart PLS 3.2.7, finally, 205 responses were analyzed. The results of the analysis showed that GHRM positively impacts the pro-environmental behavior of employees. Results show that there is a significant mediation of Green Entrepreneurship and a significant moderation of Green Self-Efficacy, respectively. This study fulfills the gaps in literature and provides pioneering inputs as there is a lack of studies in green HRM field, especially in the hospitality sector of Pakistan. This study enhances the knowledge in the green HRM field. Besides, this study also contributes practically and provides various inputs to hospitality sectors that how effective environmental performance can be enhanced by effectively incorporating green practices in the HR policies of organizations. This study is significant as it contributes to both theory and practice by providing fresh insights on green HRM.
Keywords: 650; green entrepreneurship; ability-motivation-opportunity (AMO); Green human resource management (GHRM); green self-efficacy; pro-environmental behavior